Who is prescribed valproate and how carefully is this treatment reviewed in UK mental health services? Data from a clinical audit. (July 2022) - Paton, Carol; Citrome, Leslie; Fernandez-Egea, Emilio; Rendora, Olivia; Barnes, Thomas R.E.
Background: The licensed indications for valproate are narrow, yet this medication is commonly prescribed in mental health services. Objectives: To explore the target symptoms/behaviours for which valproate is prescribed and how well the efficacy and tolerability of this treatment are monitored in routine clinical practice. Design: An audit-based quality improvement (QI) programme in UK mental health services. Methods: Information on valproate prescribing was collected from clinical records using a bespoke data collection tool. Results: Sixty-four NHS mental health Trusts/healthcare organisations submitted data on valproate treatment for 5320 patients. Valproate was clearly prescribed for a licensed indication in 1995 (38%) patients, off-label in 1987 (37%) while the indication was uncertain/not available in 1338 (25%). Of the 919 patients started on valproate treatment within the past year, between a half and two-thirds had each of the relevant baseline physical health checks documented. In 539 (59%) of these patients, valproate was prescribed for an unlicensed indication; the prescription was recognised as off-label in 363 (67%), 20 (6%) of whom were documented as having had this explained to them. Of 631 patients prescribed valproate for between 3 months and a year, early on-treatment assessments of response and side effects were documented in 441 (70%) and 332 (53%), respectively. Of 4401 patients treated for more than a year, annual on-treatment reviews of clinical response and side effects were documented in 2771 (63%) and 2140 (49%), respectively. Conclusion: Our data suggest the majority of prescriptions for valproate in mental health services are not for a licensed indication. Furthermore, patients rarely receive an explanation that their valproate prescription is off-label, perhaps partly because the licensed indications are not widely understood by prescribers. Given the very limited evidence for efficacy for the off-label uses of valproate, failure to routinely conduct early on-treatment and annual reviews of the benefits and side effects of this medication may result in patients remaining on ineffective and poorly tolerated treatment by default.